Symbiosis in the microbiome of people with asd and its effects on the brain-intestine linkage (Research, Society and Development, 2022)
Researches show that individuals with Autistic Spectrum Disorder (ASD), present an imbalance in the intestinal microbiota, by the study carried out, there is a possibility of mitigating the characteristic symptoms of Autistic Spectrum Disorder, through the symbiosis in the intestinal microbiome. The objective of this bibliographic review is to analyze the influence of symbiosis on the microbiome in the intestine-brain axis in individuals with ASD and to verify the nutritional needs of this individual, in order to support nutritional strategies. Analyzing the gut-brain axis of children with ASD, verifying the effects of symbiosis on the microbiome and the nutritional needs of autistic people. The approach of this research was qualitative, with a basic purpose, of an observational nature, being cross-sectional bibliographic research. Studies were used to investigate the effectiveness of vitamin and mineral supplementation in the diet of children with autism spectrum disorder. The present study concludes that autistic children are more deficient in the intake of vitamins and minerals, and those who are supplemented with vitamin D had reduced or absent symptoms of ASD. Thus, it will be necessary to offer a greater variety of fruits and vegetables to obtain adequate dosages of micronutrients through food intake, helping with homeostasis in the microbiota in order to achieve a symbiosis in the intestinal microbiome of the child with ASD.